A new genus of cardinalfish from tropical Australia and southern New Guinea (Percomorpha: Apogonidae) - Fraser, Thomas H. (Zootaxa, 2014)
Ozichthys is described as a new monotypic genus, type species Apogon albimaculosus. This species is restricted to tropical Australia and southern New Guinea. The combination of first dorsal fin with VIII visible spines, fused first and second hypurals, epineural on ninth rib, ossified lower preopercle edge, serrated edge of the preopercle, more than three flute canals on post orbit, 23–24 pored lateral- line scales, elongate last lateral-line scale, and sixteen rows of free neuromasts on principal caudal fin-rays will identify this genus from other brownish ground-colored apogonids. This genus is placed in the clade with Apogonichthys, Foa, Fowleria, and Neamia based on color patterns present on the head, body and vertical fins and in having a single pore above and below the raised median canal on each pored lateral-line scale.